Efektivitas Media Flashcard dalam Mengatasi Keterlambatan Membaca pada Siswa Sekolah Dasar - Atika Zata Amani; Adrias Adrias; Fadila Suciana (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to assess the effectiveness of using flashcards in overcoming reading delays in elementary school students. The method applied was a literature review by analyzing seven scientific articles published between 2020 and 2025. The results showed that the use of flashcards significantly improved students' reading skills, both in recognizing letters, words, and understanding reading. In addition, flashcards also proved effective in increasing students' motivation and interest in learning. However, their effectiveness is influenced by several factors, such as media design, teacher training and learning environment support. These findings provide valuable insights for educators in determining appropriate learning methods for students with reading delays. Therefore, this study recommends flashcards as an innovative learning media that can be customized to suit students' needs.